2010
DOI: 10.4137/bbi.s4551
|View full text |Cite
|
Sign up to set email alerts
|

Normal Mode Flexible Fitting of High-Resolution Structures of Biological Molecules toward SAXS Data

Abstract: We present a method to reconstruct a three-dimensional protein structure from an atomic pair distribution function derived from the scattering intensity profile from SAXS data by flexibly fitting known x-ray structures. This method uses a linear combination of low-frequency normal modes from an elastic network description of the molecule in an iterative manner to deform the structure to conform optimally to the target pair distribution function derived from SAXS data. For computational efficiency, the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 52 publications
0
27
1
Order By: Relevance
“…Programs have been developed to account for the solvation layer to simulate profiles that agree to the experimental data (Svergun et al, 1995;Yang et al, 2009;Schneidman-Duhovny et al, 2010). In our recent study, we attempted fitting the simulated data from CRYSOL (Svergun et al, 1995) with and without considering the scattering from the solvation layer and found that the inclusion of solvation layer improves fitting quality (Gorba and Tama, 2010). In other studies, it has been shown that the solvation layer does not significantly change the simulated intensity profile, and thus would not affect the fitting .…”
Section: Effect Of Solvation Layer In Saxs Datamentioning
confidence: 94%
See 3 more Smart Citations
“…Programs have been developed to account for the solvation layer to simulate profiles that agree to the experimental data (Svergun et al, 1995;Yang et al, 2009;Schneidman-Duhovny et al, 2010). In our recent study, we attempted fitting the simulated data from CRYSOL (Svergun et al, 1995) with and without considering the scattering from the solvation layer and found that the inclusion of solvation layer improves fitting quality (Gorba and Tama, 2010). In other studies, it has been shown that the solvation layer does not significantly change the simulated intensity profile, and thus would not affect the fitting .…”
Section: Effect Of Solvation Layer In Saxs Datamentioning
confidence: 94%
“…Thus a good protocol to terminate the iteration process is a key for successful application. In the recent application to SAXS data, we observed that the rate of change of the scoring function is a good measure to stop the fitting process (Gorba et al, 2008;Gorba and Tama, 2010).…”
Section: Termination Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical attempts have been made to combine elastic NMA with fitting to SAXS data (Gorba and Tama 2010). In that case, subsequent perturbations of a coarsegrain model along normal modes are evaluated against the P(r) function to guide the overall fitting procedure.…”
Section: Discussionmentioning
confidence: 99%